Hubungan Aktivitas Fisik Dengan Stabilitas Tekanan Darah Pada Penderita Hipertensi Di Wilayah Kerja Puskesmas Kembaran I - Rica Arafik Patturahman; Tophan Heri Wibowo; Danang Tri Yudiono (Jurnal Anestesi, 2024)
Hypertension is a disease whose prevalence always increases every year. Uncontrolled hypertension is still a major problem in efforts to treat hypertension. Lifestyle changes, one of which is physical activity, is an important part of cardiovascular therapy management and is important in controlling blood pressure. The purpose of this study was to determine the relationship between physical activity and blood pressure stability in hypertensive patients in the working area of the Kembaran 1 Public Health Center, Banyumas Regency. The research design is a correlation study survey with a cross sectional time approach. The sample in this study was hypertension recorded as Prolanis participants at the Kembaran I Health Center as many as 24 respondents with consecutive sampling technique. The research instrument used a Global Physical Activity Questionnaire (GPAQ) and a sphygnomanometer. Data analysis using lambda test. The results showed that most of the physical activity in hypertensive patients were in the moderate category (50%). Blood pressure stability in hypertensive patients was mostly in the stable category (54.2%). Lambda test results obtained p-value of 0.012 (p-value ? ?) and value of 0.455 (? 0). In conclusion, there is a relationship between physical activity and blood pressure stability in hypertensive patients in the Kembaran 1 Public Health Center, Banyumas Regency.